Meninjau Kembali Hubungan Agama dan Politik dalam Kerangka Demokrasi dan Keadilan - Sunaryo Sunaryo (IAIN Ponorogo, 2020)
Abstract: Through this article, I try to revisit the relationship between religion and politics. There are three main ideas I propose here. First, about the nature and function of religion for human beings. Once, many scholars have predicted that religion would disappear from human life that was increasingly modernized and rationalized. But in fact, religion has not really disappeared. The prediction is wrong because it is not based on the nature of human beings who always have a desire for the Transcendent. Secondly, in the history of secularization in Europe that has been going on for several centuries, it did not completely nullify religion from public life. Religion is still present in forms that have been adjusted to democratic values. Some religious symbols are also still used. Third, I don’t argue that religion needs to be incorporated into politics. What I want to deliver here is that we need to see the relationship proportionately. Religious groups have the right to propose their religious views in the public sphere. But at the same time, they need to develop reasonable arguments. They should translate their religious values to be compatible with the values of democracy and justice in a pluralistic society.